Identity and belonging in the work of entrepreneurs and factionalists in the intimate fashion sector (Management and Connections Journal, 2026)
The objective of this work is to understand work as a source of personal development, belonging, and the constitution of identities of entrepreneurs and factionalists in the intimate fashion sector. The methodological strategy was qualitative and descriptive. Data were collected through semi-structured interviews and treated based on content analysis. The results indicate that the relationship of women with work permeates the dimension of belonging and is a preponderant factor in the construction of their identities. When comparing the reality of factionists and female entrepreneurs, there is a presence of belonging and social value through work, more evident among female entrepreneurs. The contribution of this study is to discuss the reality of a socioeconomic context with specific challenges, to point out the differences in possibilities and challenges of female work related to two groups: entrepreneurs and factionists, in addition to deepening the discussion on identity at work and belonging.
Keywords: identity at work; woman; associativism; women entrepreneurs; faccionistas